LEGAL PROTECTION OF THE CREDITOR ON FIDUCIARY GUARANTEE OBJECTS UNLISTED IN THE FIDUCIARY REGISTRATION OFFICE - Sanusi Sanusi (UNISSULA, 2017)
The aim of this study was to analyze the legal protection of the creditor and their weaknesses on the fiduciary guarantee objects unlisted in the current Fiduciary Registration Office. This study is a normative legal research or also called doctrinal legal research. This research will use facts that describe the legal protection of the creditor on the fiduciary guarantee objects unlisted in the current fiduciary registration office, the weaknesses of legal protection of the creditor on the fiduciary guarantee objects unlisted in the current fiduciary registration office, and the reconstruction of the legal protection of the creditor on the fiduciary guarantee unlisted in the fiduciary registration office based on the value of justice. The result of the research is that the Government should immediately establish the Supervisory Agency and Execution of Fiduciary Guarantee Objects based on Government Regulation in Lieu of Law and other legislation.